1994
DOI: 10.1111/j.1476-5381.1994.tb17144.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of thrombosis and rethrombosis and enhancement of the thrombolytic actions of recombinant tissue‐type plasminogen activator in the canine heart by DMP728, a glycoprotein IIb/IIIa antagonist

Abstract: 1 We studied DMP728, a non-peptide glycoprotein (GP) IIb/IIIa receptor antagonist, for prevention of coronary artery thrombosis or rethrombosis in a chronic canine model subjected to arterial injury. 2 In protocol I, DMP728 (1.0mg kg-', i.v., n = 8) or saline (n = 8) was administered and a 150 JA anodal current was applied to the intimal surface of the left circumflex coronary artery (LCX). Dogs were monitored for 6 h and again on each of 5 subsequent days. 3 Ex vivo platelet aggregation was inhibited but retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
3
4
0
Order By: Relevance
“…Thus, CRL42796 displays a rapid‐on and rapid‐off pharmacological profile that may offer an improved safety factor in those clinical situations where increased bleeding might occur. Other GPIIb/IIIa receptor antagonists such as 7E3 (Bates et al ., 1992; Rote et al ., 1994c), DMP‐728 (Lucchesi et al ., 1994), and SM‐20302 (Huang et al ., 1999) result in extended maintenance of vessel patency despite the fact that ex vivo platelet aggregation responses return to baseline values. There are other factors to consider involving a time‐dependent decrease in the thrombogenicity of the injured vessel wall thus allowing preservation of blood flow in the presence of normal platelet function.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, CRL42796 displays a rapid‐on and rapid‐off pharmacological profile that may offer an improved safety factor in those clinical situations where increased bleeding might occur. Other GPIIb/IIIa receptor antagonists such as 7E3 (Bates et al ., 1992; Rote et al ., 1994c), DMP‐728 (Lucchesi et al ., 1994), and SM‐20302 (Huang et al ., 1999) result in extended maintenance of vessel patency despite the fact that ex vivo platelet aggregation responses return to baseline values. There are other factors to consider involving a time‐dependent decrease in the thrombogenicity of the injured vessel wall thus allowing preservation of blood flow in the presence of normal platelet function.…”
Section: Discussionsupporting
confidence: 93%
“…YM337 accelerated tPA-induced thrombolysis and prevented acute reocclusion after successful thrombolysis. Similar results have been reported for many studies on the effectiveness of c7E3 and other GPIIb/IIIa antagonists (20)(21)(22)(23)(24). The efficacy of aspirin after thrombolytic therapy in the prevention of reinfarction has been confirmed clinically (25).…”
Section: Discussionsupporting
confidence: 89%
“…These studies showed the combination of 7E3 F[ab']z or c7E3 and t-PA to restore coronary perfusion rapidly and to nearly abolish the occurrence of reocclusion. Similar findings were observed using short, synthetic peptide, reversible inhibitors of the IIb/IIIa receptor (35,36).…”
Section: Enhancement Of Thrombolysissupporting
confidence: 81%